Agent-based modelling of the spatial pattern of leisure visitation in forests: A case study in Wallonia, south Belgium. (September 2015) - Li, Sen; Colson, Vincent; Lejeune, Philippe; Speybroeck, Niko; Vanwambeke, Sophie O.
Abstract: The leisure use of forests is a fast growing sector in European tourism. The difficulties in monitoring real usage pattern have hindered communications in tourism, conservation and public health in forested areas. In this study, we present an agent-based model to approximate forest visit patterns at the regional level, based on the visitor, residential and forest attributes. The model was then adapted locally for Wallonia, south Belgium, to predict the daily distribution of forest visits and visitor flows. The results suggest high visit rates in urban forests. In highly attractive forests that are distant from major cities, the visit rates may greatly respond to the visitor-level and environmental changes. Future empirical investigations are encouraged to build a cross-contextual understanding on visitors' decision-making mechanisms and to identify how these mechanisms may be influenced by environmental factors operating at different spatio-temporal levels. Highlights: Development of an agent-based model for daily leisure visitation patterns in forest. Visitor, residential and woodland attributes guided the agents' decision-making. The model predicted forest visitation patterns in the Walloon region of Belgium. Urban forests had high predicted visit rates. Visit rates in remote but attractive forests were highly sensitive to environmental changes.